Solid state and dissolution behaviour of a low melting point drug in co-milled mixtures of Sesamum radiatum gum - Seham Shaboun; Elijah Nep; Ndidi C. Ngwuluka; Adeola Adebisi; Barbara Conway; Alan Smith; Kofi Asare-Addo (British Journal of Pharmacy, 2018)
The search for non-toxic and cost effective carriers for solid dispersion formulations has increased the focus of researchers on renewable resources. In this study, gum was extracted from the leaves of Sesamum radiatum (SRG) and its role in solid dispersion formulations of Ibuprofen (IBU) investigated. Physical mixing and comilling using different ratios of IBU to SRG (4:1, 1:1, 1:4) and milling times of 1 min, 5 min, and 10 min was employed. Solid state of these formulations was characterized using DSC, FT-IR and XRPD. The effect of the co-milling ratio and time on drug dissolution was also studied. Solid state characterization showed that SRG does not interact with IBU in the solid dispersion formulations. However, SRG retarded the release of IBU from all the formulations. Although the co-milled solid dispersions gave a higher dissolution than the physical mixes (PM), with the dissolution rate increasing as the ratio of SRG decreases, the technique did not result in appreciable improvement in the dissolution of IBU. The gel layer that surrounded the formulations suggest SRG may prove useful as a hydrophilic carrier in matrices for extended release and perhaps a modified form of the gum could be used in solid dispersions.